Revision of the New Caledonian genus Mecynostomella (Trichoptera, Kokiriidae) - Johanson, Kjell Arne (Zootaxa, 2003)
The genus Mecynostomella Kimmins, 1953 is revised. Six new species are described: Mecynostomella sigma sp.n., M. hollowayi sp.n., M. brevis sp.n., M. caledonia sp.n., M. spinosa sp.n., and M. flinti sp.n. The diagnosis of Mecynostomella is modified due to the new findings and distribution maps of the Mecynostomella species are presented. A key to males of all species of Kokiriidae is presented.